Understanding the relationship between networks and technology, creativity and innovation - Aharonson, Barak S. (Technology, innovation, entrepreneurship and competitive strategy,, 2013)
An exciting new volume in the Technology, Innovation, Entrepreneurship and Competitive Strategy series from Emeralds popular Strategy collection. This volume features excellent new research devoted to advancing our understanding of how networks foster creativity, innovation and the development of cutting-edge technologies. Contributions offer unique perspectives on the significance of networks to the financial success of businesses, in addition to giving examples of how these can be crucial in bringing about creativity and innovation. It deals with the evolution of networks through geographic and industry boundaries. This is crucial reading for any researchers exploring strategic management tools and techniques, and specifically the intricacies of "network theory" within businesses.